CRP Levels during First Trimester of Pregnancy is Associated with Preterm Labor and Low Birth Weight - Mohammadi B; Moghaddam Banaem L; Asghari M (Tehran University of Medical Sciences, 2010)
Background & Objective: Preterm labor is a major risk factor of mortality and morbidity in newborns and fetuses. Low birth weight is also a risk factor for mortality and various neonatal diseases. This study aimed to determine the association between the CRP levels in first trimester of pregnancy with low birth weight and preterm labor. Methods & Materials: In this prospective cohort study, we measured serum CRP levels in 400 pregnant women up to 20 weeks of gestation. All participants were followed up to delivery. Preterm labor was defined as delivery before 37 weeks of gestation. Low birth weight was defined as weight less than 2500 g at birth. Statistical analysis was done using Chi-square, Logistic regression, and ROC curve. P-values less than 0.05 were considered to be significant. Results: After controlling for the effects of age above 35 years, mothers' occupations, history of preterm labor, socio-economic status, history of abortion, primiparity, and passive smoking, logistic regression analysis showed statistically significant relationship between the CRP and preterm labor (P-value=0.000, OR=1.24, %95 CI=1.11-1.38). However, there were no significant relationships between the CRP levels with other factors. Using Roc curve, we determined CRP cut-off point level for preterm labor. With 81% sensitivity, and 64% specificity, CRP cut-off point was 3.45 mg/l. After controlling for the effects of low socio-economic status, history of LBW, history of abortion, gravidity, primiparity, and passive smoking, logistic regression analysis showed statistically significant association between the CRP levels and LBW (OR=1.31, CI %95=1.08-1.59, P=0.005). However, there were no significant relationships between CRP levels with other factors. CRP cut-off point level for LBW was determined using Roc curve. With 87.5% sensitivity, and 74% specificity, CRP cut-off point was 4.75 mg/l. Conclusion: It seems that the inflammatory marker, CRP, can be used to identify women who are at high risk for preterm labor and LBW. However, larger studies are needed to establish this relationship definitively